Asymptotics for the Complexity of Boolean Functions with Small Number of Ones - Red’kin, N. P. (Mathematical Notes, 2021)
The class of Boolean functions consisting of all functions of variables each of which outputs at exactly -tuples of values of the variables is considered. For small , for example, for , an asymptotics for the complexity of implementation of every function in by a circuit of functional elements in an irredundant basis containing and is found.